The chemoattractant potential of ginsenosides in the ginseng – Pythium irregulare pathosystem. (February 2016) - Ivanov, Dimitre A.; Georgakopoulos, Jorge R.C.; Bernards, Mark A.
Graphical abstract: Treatment of ginseng roots with ginsenosides delays infection by the root pathogen Pythium irregulare, as monitored by the chlorophyll fluorescence parameter ΦNO. Highlights: High levels of ginsenosides in the soil around ginseng roots delay infection by Pythium irregulare . Crude ginsenosides promote growth of Pythium irregulare in vitro . Ginsenoside F2 inhibits growth of Pythium irregulare in vitro . Abstract: Ginsenosides produced by ginseng ( Panax quinquefolius L.) are mildly fungitoxic saponins; however, exposure of the ginseng root pathogen Pythium irregulare Buisman to ginsenosides enhances its growth in a dose dependent manner, leading to speculation that ginsenosides may function as chemoattractants and/or growth regulators in the context of the ginseng – P. irregulare pathosystem. In the present work, it was demonstrated that the treatment of ginseng plants with a relatively high dose of ginsenosides by dipping their roots into a solution of ginsenosides prior to planting results in delayed infection by P. irregulare in pot experiments, as monitored by non-invasive chlorophyll fluorescence imaging. In an attempt to determine whether this observation results from a protective effect of the ginsenosides, or from a modification of P. irregulare growth habit in response to ginsenosides present in the soil, standard in vitro disk diffusion assays were conducted. Here, exposure of P. irregulare to crude ginsenosides or pure ginsenoside Rb1, resulted in delayed hyphal progression, while enhancing aerial hyphae build-up around ginsenoside-treated disks. By contrast, assays with pure ginsenoside F2 resulted in clear zones of inhibition around treated disks. While it remains unclear whether ginsenosides act as chemoattractants for P. irregulare in vivo, the results here suggest that these saponins serve to alter the growth habit of this organism, both in vivo and in vitro .